Design and fabrication of sorting system on conveyor belt - Ahammad, Asif; Shimanto, MD.; Tasdid, Akib Hossain; Mahmud, Arman Bin (Brac University, 2024)
This final year design project is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Electrical and Electronic Engineering, 2024.